Analisis Ekonomi Pengoperasian Ketel Uap Bantu Laboratorium Permesinan Kapal Polimarin Dengan Variasi Bahan Bakar - Susanto Santo; Okpina Rochadian; Fajar Pujiyanto (PPPM Polimarin, 2023)
Heat energy and steam pressure are very important properties in various life applications. The steam production process in a boiler can occur in a container or in a pipe. Fuel as a source of chemical energy for steam boilers can use solid, liquid or gas types. The use of solid fuel is relatively easier to use, by simply putting it into the fire kitchen. Use of gas as boiler fuel can use a gas burner as in a gas stove. The type of fuel oil used as boiler fuel is diesel oil. Diesel oil in order to be used as boiler fuel requires a burner as a fogger combined with compressed air. This study was conducted for the purpose of studying the performance of the boiler when operated from cold conditions to the maximum achievable pressure. Specifically, to determine the specific fuel consumption and the amount of fuel cost required. The experimental method was chosen for the study. Steam pressure and the amount of fuel required during combustion and steam production were the two parameters measured. There are 3 types of diesel oil grades that will be analysed in this study. Fuel type and quality affect the time required to reach maximum pressure. Bio diesel takes the longest time, dexlite takes a shorter time, and pertamina dex takes the shortest time. Total difference in fuel consumption for one operation of bio diesel oil, dexlite, and pertamina dex is 4.68, 4.38, and 4.19 litres respectively. The amount of cost required to pay for bio diesel oil, dexlite, and pertamina dex is Rp 31,824, Rp 62,415, and Rp 64,526 for one operation respectively. Fuel consumption for laboratories is recommended to use dexlite with better quality than bio diesel at a lower price than using Pertamina dex.